ON THE BIOLOGY OF PSETTODES ERUMEI (BLOCH & SCHN.), AN INDIAN HALIBUT - Das, M; Mishra, B (Indian Journal of Fisheries, 2011)
Studies on the biology of flatfisheshave made remarkable progress due to thecontribution of Dawes (1930), Jones (1952),Bagcnal (1957,1958,1962), Pitt (1964), Ryland(1966), Nordeng and Bratland (1971), Last(1978), Anon. (1980) and Liewes (1984).